Urban transportation and logistics : health, safety, and security concerns - Taniguchi, Eiichi; Fwa, Tien Fang, 1951-; Thompson, Russell G., 1962- (Engineering professional collection, 2013)
"Urban transport and logistics systems play a very important role in delivery goods and services both into populous areas as well as out to local and regional areas. This book takes global approach to best practices, covering topics such as hazmat transport, logistics during disasters, mixed traffic and safety considerations, optimizing vehicle routing and scheduling, and road safety. These subjects provide an important basis for discussing transport and logistics systems in urban areas from the viewpoint of safety and security considerations on human life."--